Nutrition at Early Stages of Life Determines the Future Growth and Reproductive Performance of Dairy Calves - Philipe Moriel; Luiz Ferraretto (EDIS)
Nutrition prior to weaning (1 to 45 to 60 days of age) may determine the future performance of dairy calves. Good quality colostrum management is required to maximize health, but also impacts the growth and reproductive performance of calves. Providing an intensive nutritional method by increasing the amount and nutritional composition of milk replacer and calf starter provided from birth to weaning, enhances pre-weaning growth performance, anticipates puberty achievement and increase future milk production, without impairing mammary gland growth.